Model-based safety assessment method of civil aircraft power distribution network - ZHANG Yuan; HAN Weixin (Xibei Gongye Daxue Xuebao)
With the continuous development and continuous innovation of aviation technology, the complexity and integration of civil aircraft's power distribution network system are getting higher and higher. Therefore, its safety plays a crucial role in ensuring the safe operation of aircraft. Traditional safety assessment methods rely heavily on the engineering experience of engineers. The complex cross-linking of distribution networks reduces the effectiveness and efficiency of the safety assessment and brings difficulties to subsequent iterations. Model-based safety analysis(MBSA) can effectively reduce the complexity of analysis and iteration, and it can improve the efficiency and accuracy of safety assessment. The MBSA method is introduced. Then, the model-based safety assessment of a civil aircraft distribution network is carried out. The modeling analysis and evaluation process are constructed based on fault logic modeling. The evaluation results are presented, and further comprehensively evaluated based on expert weights. It is proven that MBSA is effective for the safety assessment of actual power distribution systems.